Nurses' experiences of an abortion counselling training course and their understandings of quality abortion services - Mogonong, Laurah Carolina (Rhodes University, Faculty of Humanities, Department of Psychology)
This research study focuses on nurses' experiences of participating in an abortion counselling training programme in the Eastern Cape Province (E.C), using a grounded theory and symbolic interactionism framework. The study aims to investigate how participating in a women-centred abortion counselling training course offered through the Critical Studies in Sexualities and Reproduction research unit may modify or improve nurses' practice of abortion counselling and understanding of quality abortion services. Through purposive sampling, nine research participants working as abortion providers in EC health care facilities were recruited. Research data were produced using discussions around prior abortion counselling experiences, a reflective activity, power point case presentations conducted within the counselling training, and semi-structured interviews conducted two months after the training with five of the providers. A grounded theory analysis was used to generate themes that highlighted different aspects that enabled or hindered access to quality abortion services. In accordance with prior research, it was revealed that nurses undergo abortion training but there is limited content on abortion counselling training. Findings from this study reveal the modifications of practice and understanding of quality abortion services of nurses who participated in the client-centred abortion counselling training course. Themes of change that emerged from the nurses' experiences were rendering counselling services in a non- judgemental, non-directive way, being acknowledged and recognized for the services they offer as abortion providers, and accepting that abortion is a reproductive legal right that can be accessed whenever a woman in need of the service requests it. The findings of this research also indicate that, despite the controversy and stigma attached to providing abortion services, the participants were motivated to continue offering abortion services because they felt equipped since undergoing abortion counselling training. The training course improved reported abortion counselling practices, but systematic issues such as lack of managerial support, space for individual counselling and procedure equipment continue to undermine services.
Keywords: Abortion counseling; Abortion Psychological aspects; Nurses Attitudes; Abortion services -- South Africa -- Eastern Cape; Grounded theory; Person-centered therapy